Availability and Use of an Automated External Defibrillator at Emergency Medical Dispatch. (3rd September 2019) - Gardett, Isabel; Broadbent, Meghan; Scott, Greg; Clawson, Jeff J.; Olola, Christopher
Abstract: Objective : The aim of this study was to determine the frequency of automatic external defibrillator (AED) retrieval and placement by bystander callers when prompted by an Emergency Medical Dispatcher (EMD).Methods : This retrospective descriptive study utilized a convenience sample of emergency dispatch data collected from 23 Emergency Communication Centers (ECCs) spanning 14 states across the United States (U.S.) from July 11, 2014 to August 13, 2018, including all cases in which the EMD recorded any response to the AED availability prompt. Data were collected using ProQA, the software version of the Medical Priority Dispatch System. Primary outcome measures were (a) distribution of responses to the AED prompt; (b) percentage of cases in which an AED was retrieved; and (c) percentage of cases in which AED pads were placed by the bystander-caller.Results : A total of 2, 200, 285 cases were collected during the study period, in 18, 904 (0.86%) of which the AED prompt was displayed (indicating suspected out of hospital cardiac arrest, or OHCA). Overall, an AED was reported as available 5.8% ( n  = 1, 091) of the time the EMD recorded an answer to the AED prompt. In multiple-rescuer situations, a rescuer was sent to get the AED 2.8% ( n  = 523) of the time, as opposed to only 0.30% ( n  = 56) for single-rescuer calls. The AED was reported to be already on scene, by the patient, in 2.7% ( n  = 512) of the cases. A majority (72.0%; n  = 417) of the time, rescuers who were sent to get an AED were unable to retrieve it, with single rescuers being successful more often (57.1% unable to retrieve, vs 73.6% for multiple rescuers).Conclusions : AEDs are reported as available by only a small percentage of callers to 911, and in the majority of cases in which a bystander rescuer is sent to retrieve an AED, one is never located or used. Sending someone to retrieve the AED may be more appropriate in multiple-rescuer situations than when a single bystander rescuer is alone on scene.